Simultaneous analysis of indaziflam and its metabolites in pitaya using dispersive solid phase extraction coupled with liquid chromatography coupled with tandem mass spectrometry. Issue 19 (20th August 2019) - Liu, Xiaoliang; Ji, Chunhong; Tang, Wenwei; Hu, Mingfeng; Tan, Huihua; Li, Xuesheng; Ma, Shaozhi; Yu, Xiangyang; Zeng, Dongqiang
Abstract: A simple and efficient multiresidue method using dispersive solid phase extraction and liquid chromatography coupled with tandem mass spectrometry was developed for the targeted analysis of indaziflam and its five metabolites (indaziflam‐diaminotriazine, indaziflam‐carboxylic acid, indaziflam‐triazine indanone, indaziflam‐hydroxyethyl, and indaziflam‐olefin) in pitaya samples (including roots, plants, flowers, peels, pulp, and whole fruit). The analytes were extracted with acetonitrile, and the extracts were purified using multiwalled carbon nanotubes. The method was validated using pitaya samples spiked at 0.5, 5, and 50 µg/kg, and the average recoveries varied from 61.1 to 103.7% with relative standard deviations lower than 12.7% ( n  = 5). This method exhibited sufficient linearity within the concentration range of 0.1–100 µg/L. The limits of detection and quantification were in the ranges of 0.001–0.1 and 0.003–0.3 µg/kg, respectively. The method was successfully applied to analyze pitaya samples in Nanning, and no indaziflam or its metabolites were detected in the samples analyzed.